Ethical Aspects of Climate Engineering - Betz, Gregor (KIT Scientific Publishing, 2012)
This study investigates the ethical aspects of deploying and researching into so-called climate engineering methods, i.e. large-scale technical interventions in the climate system with the objective of offsetting anthropogenic climate change. The moral reasons in favour of and against R&D into and deployment of CE methods are analysed by means of argument maps. These argument maps provide an overview of the CE controversy and help to structure the complex debate. Arguments covered in this analysis include: The central justification of R&D; side-effects of R&D and of deployment; lesser-evil argumentation; two-degree target argumentation; efficiency and feasibility considerations; arguments from ethics of risk; arguments from fairness; geo-political objections; critique of technology and civilization; religious, existentialist, and environmental-ethics arguments; alternative justifications of R&D; lack of R&D alternatives; direct justifications of R&D prohibition; priority of mitigation policies.